Optimal planning of hybrid photovoltaic/battery/diesel generator in ship power system - Abba Lawan Bukar; Chee Wei Tan; Kwan Yiew Lau; Ahmed Tijjani Dahiru (Institute of Advanced Engineering and Science, 2020)
In line with the increasing concern on the pollution release by marine ships, renewable energy technologies in ships power system has received so much attention. Recently, photovoltaic (PV) and energy storage system (ESS) are been integrated into conventional diesel generator in ships power system Nevertheless, improper sizing of the overall ship power station will result in a high investment cost and increase CO2 emission. This paper devised a methodology to compute the optimal size of the ESS, PV and diesel generator in a ship power system to minimize CO2 emission, fuel cost, and investment cost. It is a well-known fact that power generation in a sailing ship depend on the time zone, local time, date, latitude, and longitude along ship navigation route and the condition of the ship power system also differs from power systems on land. The devised method in this paper takes into accounts the geographical and season variation of solar insolation along the route from Lagos (Nigeria) to Conakry (Guinea) and accurately model the power output of PV modules is along the route.